Encyclopedia of Animal Cognition and Behavior 2020
DOI: 10.1007/978-3-319-47829-6_2089-1
|View full text |Cite
|
Sign up to set email alerts
|

Schedule-Induced Behavior

Abstract: Schedule induction refers to the process of behavior being developed during inter-reinforcement intervals without explicit arranged contingency between its occurrence and the delivery of reinforcement but only by the repeated occurrence of intermittent scheduled reinforcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
2
2
1
Order By: Relevance
“…Moreover, animals treated with THC had higher percentages of entries in bins 30 and 3 -the moments that were closer to the reinforcer delivery-with respect to the same bins in control sessions. This result is consistent with the explanation that all the behaviours generated within inter-food intervals compete for their manifestation during the interval and tend to organize in a sequential manner (Pellón et al 2020). SID behaviour competes with magazine entries, lever presses, or wheel running, thus displaying different temporal patterns to one another (Gutiérrez-Ferre 2019; Pellón and Killeen 2015).…”
Section: Declarationssupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, animals treated with THC had higher percentages of entries in bins 30 and 3 -the moments that were closer to the reinforcer delivery-with respect to the same bins in control sessions. This result is consistent with the explanation that all the behaviours generated within inter-food intervals compete for their manifestation during the interval and tend to organize in a sequential manner (Pellón et al 2020). SID behaviour competes with magazine entries, lever presses, or wheel running, thus displaying different temporal patterns to one another (Gutiérrez-Ferre 2019; Pellón and Killeen 2015).…”
Section: Declarationssupporting
confidence: 88%
“…SID displays a distinctive temporal pattern in the form of an inverted U-shaped function as the time between food deliveries elapses (Pellón et al 2020). During the last SID session in the present study, the temporal distribution of licking showed an identical shape when the saline injection session was compared with the last day of SID acquisition in any of the three groups of the experiment; vehicle administration did not affect it either.…”
Section: Discussioncontrasting
confidence: 37%
See 1 more Smart Citation
“…Lever-pressing rate was similar among groups although slightly higher for the NW groups, whereas licking rate was higher for W15 than for the other W groups. Licking rate, when measured in licks/min, is often reported higher for FI 30 s than for FI 15 s and lower for FI 60 s (Flores & Pellón, 1997; Pellón et al, 2020), but on many occasions the highest rate of responding corresponds to the highest reinforcement frequency (Castilla & Pellón, 2013; Íbias & Pellón, 2011, 2014), as has been the case in the present study. Based on reinforcement frequency as a controlling variable, it is reasonable to find a positive relation between response and reinforcement rates, and when this does not occur it could be likely attributable to response competition interfering with licking (such as from lever pressing, magazine entering or eating).…”
Section: Discussionsupporting
confidence: 68%
“…Schedule-induced behaviors (previously known as adjunctive) are those that develop at an excessive rate during the interreinforcement interval of an intermittent reinforcement schedule without having an explicit arranged contingency between its occurrence and reinforcer delivery (Pellón et al, 2020). Although the development of schedule-induced behaviors has been widely documented (for some revisions, see, Falk, 1971; López-Tolsa, 2019; Pellón, 1990; Roper, 1981), there is still no agreement as to why they occur and how they are maintained.…”
mentioning
confidence: 99%